Analysis of Exchange Rate, Inflation, and Benchmark Interest Rate Impacts on the IDX Composite Index Before and After the COVID-19 Pandemic in the Years of 2019-2021 - Shatria, Alifio Ananda; Taufiq, M. (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2024)
This research examines the impact of inflation, exchange rate, and Bank Indonesia (BI) interest rate on the IDX Composite Index before and during COVID-19. This research's subjects include companies listed on the IDX Composite Index on the Indonesia Stock Exchange (IDX) from 2019 to 2021, spanning a 36-month sample period. This research employs quantitative methods such as multiple linear regression, correlation, multicollinearity, and heteroscedasticity as the classical assumption testing. The coefficient determination test, t-test, and F-test are all part of hypothesis testing. The findings of this research show that inflation and the BI rate have a simultaneous effect due to the influence of the currency rate. All three variables: inflation, currency rate, and BI rate could all have an impact on the IDX Composite Index before and during COVID-19 between 2019 and 2021.